How leader member exchange affects effectiveness of performance appraisal system: A chain of reactions model - Muhammad Waqas Maharvi; Aneel Kumar; Khalil Ahmed Channa; Ayaz Mahmood (Cogent Business & Management, 2023)
The main purpose of the current study was to evaluate the effectiveness of performance appraisal system that highlights the role of performance appraisal reactions (i.e. performance appraisal fairness and performance appraisal satisfaction) in the relationship between leader-member exchange and effectiveness of performance appraisal. Fairness of performance appraisal reactions (i.e. distributive and procedural) mediates at step one and satisfaction with performance appraisal reaction mediates at step two, in a serial mediation model. The study was a cross-sectional quantitative study in which survey approach was used for data collection. The data were collected through a survey questionnaire, from 557 teachers, working in school education department of Punjab, Pakistan, using proportionate random sampling technique. The findings of this study showed the significant effect of the quality of the leader member exchange relationship on effectiveness of performance appraisal system. Further, in a serial mediation model, performance appraisal reactions, i.e. fairness of performance appraisal (distributive and procedural), were found as mediators at step one and satisfaction with performance appraisal as mediator at step two in the aforementioned relationship.
Keywords: 650; distributive and procedural fairness; effectiveness of performance appraisal system; leader member exchange; performance appraisal satisfaction